Advanced monitoring and procedures for small animal emergency and critical care - Creedon, Jamie M. Burkitt; Davis, Harold 1958- (Wiley-Blackwell, 2023)
"The word "triage" comes from the French verb trier, meaning to sort. The concept of triage finds its origin in the military, and the goals of triage in human medicine have varied over the years depending upon the situation. After World War II triage came to mean the process of identifying those soldiers most likely to return to battle after medical care. During the Korean and Vietnam conflicts the goals of triage came to mean the greatest good for the greatest number of wounded. In times of disaster, the goals of triage are like those of the military: to concentrate effort and resources on saving the largest number of people possible. Daily human emergency room triage began in the 1960s and has evolved into a method to separate efficiently those patients stable enough to wait for treatment from those who require immediate medical attention. In veterinary medicine we have adopted the goals of our counterparts in the human emergency room. Thus, we prioritize cases by medical urgency when presented with multiple emergencies at the same time"--